2001
DOI: 10.1103/physrevd.64.034007
|View full text |Cite
|
Sign up to set email alerts
|

QCD at small nonzero quark chemical potentials

Abstract: We study the effects of small chemical potentials associated with the three light quark flavors in QCD. We use a low-energy effective field theory that solely relies on the symmetries of the QCD partition function. We find three different phases: a normal phase, a pion superfluid phase and a kaon superfluid phase. The two superfluid phases are separated by a first order phase transition, whereas the normal phase and either of the superfluid phases are separated by a second order phase transition. We compute th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
235
6

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(259 citation statements)
references
References 24 publications
18
235
6
Order By: Relevance
“…In [4] this theory was studied in detail for N f = 3. It was found that a phase transition to a kaon condensed phase takes place at µ = M. For µ < M the saddle point of the static part of the effective Lagrangian is given by the identity matrix.…”
Section: Kaon Condensation In Qcdmentioning
confidence: 99%
See 4 more Smart Citations
“…In [4] this theory was studied in detail for N f = 3. It was found that a phase transition to a kaon condensed phase takes place at µ = M. For µ < M the saddle point of the static part of the effective Lagrangian is given by the identity matrix.…”
Section: Kaon Condensation In Qcdmentioning
confidence: 99%
“…For convenience, this quark will be identified as a strange quark. It is now well understood how to extend a chiral Lagrangian to nonzero chemical potential [20,18,3,2,4,19,21]: Requiring QCD and the low-energy effective Lagrangian to have the same transformation properties of a local external vector source uniquely determines the dependence of the chiral Lagrangian on this vector source and thus on the chemical potential. No additional parameters are necessary.…”
Section: Kaon Condensation In Qcdmentioning
confidence: 99%
See 3 more Smart Citations